Oil-detachment from the calcium carbonate surfaces via the actions of surfactant, nanoparticle and low salinity brine: An insight from molecular dynamic simulation. (20th July 2019) - Aminian, Ali; ZareNezhad, Bahman
Graphical abstract: Highlights: MD simulation for the low salinity surfactant containing nanoparticles for EOR. The efficiency of the LSS + TiO2 NPs evaluated by IFT and contact angle. Carbonate reservoir conditions and variety of salts and oil components considered. Synergy between NPs and surfactant along with Mg 2+ and SO4 2− is observed. Abstract: The molecular dynamic simulation of oil detachment from the calcium carbonate solid surface employing nanoparticles, an ionic surfactant and low salinity brine at petroleum reservoir operating conditions is investigated in this work. All molecular, atomic and ionic force fields and fluids-rock surface interactions are rigorously simulated in the present work. The simulation results indicate that both nanoparticle sand surfactant are adsorbed at the interface between oil and aqueous brine solution such that a reduction of interfacial tension and an increase in total surface pressure lead to the oil detachment. Synergetic effect of nanoparticle, surfactant and ionic species on the alteration of rock surface wettability from oil-wet to water condition is also demonstrated by the proposed approach. The proposed molecular simulation is quite useful for assessment of the performance of complex injecting fluids regarding the oil detachment from calcium carbonate surface at reservoir operating conditions.